Boosting additive circular economy ecosystems using blockchain: An exploratory case study. (January 2023) - Ferreira, Inês A.; Godina, Radu; Pinto, António; Pinto, Pedro; Carvalho, Helena
Graphical abstract: Highlights: A real case study related to a circular economy ecosystem is developed. Plastic materials can be used as by-product in additive symbiotic networks. The requirements for blockchain technology in an additive symbiotic network are proposed. A permissioned blockchain supports the main activities in an additive symbiotic network. Blockchain technology is an enabler for promoting additive circular ecosystems. Abstract: The role of new technologies such as additive manufacturing and blockchain technology in designing and implementing circular economy ecosystems is not a trivial issue. This study aimed to understand if blockchain technology can be an enabler tool for developing additive symbiotic networks. A real case study was developed regarding a circular economy ecosystem in which a fused granular fabrication 3D printer is used to valorize polycarbonate waste. The industrial symbiosis network comprised four stakeholders: a manufacturing company that produces polycarbonate waste, a municipality service responsible for the city waste management, a start-up holding the 3D printer, and a non-profit store. It was identified a set of six requirements to adopt the blockchain technology in an additive symbiotic network, bearing in mind the need to have a database to keep track of the properties of the input material for the 3D printer during the exchanges, in addition to the inexistence of mechanisms of trust or cooperation between well-established industries and the additive manufacturing industry. The findings suggested a permissioned blockchain to support the implementation of the additive symbiotic network, namely, to enable the physical transactions (quantity and quality of waste material PC sheets) and monitoring and reporting (additive manufacturing technology knowledge and final product's quantity and price). Future research venues include developing blockchain-based systems that enhance the development of additive symbiotic networks.